WILLIAM WALLER HENING, 1 THE STATUTES AT LARGE; BEING A COLLECTION OF ALL THE LAWS OF VIRGINIA, FROM THE FIRST SESSION OF THE LEGISLATURE, IN THE YEAR 1619, at 127 (1823) (enacted 1623). - (:unkn) unknown (My University, 1623)
Ordering that no man go to work or be sent abroad without being sufficiently well-armed.
Keywords: REQUIRED POSSESSION